2022
DOI: 10.1186/s13075-022-02905-8
|View full text |Cite
|
Sign up to set email alerts
|

Osteophytes mediate the associations between cartilage morphology and changes in knee symptoms in patients with knee osteoarthritis

Abstract: Aims To investigate whether the associations between cartilage defects and cartilage volumes with changes in knee symptoms were mediated by osteophytes. Methods Data from the Vitamin D Effects on Osteoarthritis (VIDEO) study were analyzed as a cohort. The Western Ontario and McMaster Universities Osteoarthritis Index was used to assess knee symptoms at baseline and follow-up. Osteophytes, cartilage defects, and cartilage volumes were measured using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…Our experiments demonstrated also that inclusion of menisci led to a greater performance improvement than inclusion of cartilage. A study of Fan et al 4 similarly suggested that medial meniscal extrusion has a stronger association with OST formation than cartilage, at least, in symptomatic knees. Moreover, Hada et al 29 observed a strong association between medial meniscal extrusion and TM OST for early‐OA patients, measured from MRI‐based T2 maps (More detailed analysis of the correlation between meniscal damages and TM OST can be found in Supp.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Our experiments demonstrated also that inclusion of menisci led to a greater performance improvement than inclusion of cartilage. A study of Fan et al 4 similarly suggested that medial meniscal extrusion has a stronger association with OST formation than cartilage, at least, in symptomatic knees. Moreover, Hada et al 29 observed a strong association between medial meniscal extrusion and TM OST for early‐OA patients, measured from MRI‐based T2 maps (More detailed analysis of the correlation between meniscal damages and TM OST can be found in Supp.…”
Section: Discussionmentioning
confidence: 97%
“…OSTs are strongly associated with the presence of knee pain and often with other symptoms 4–6 . For instance, presence of femoral OSTs, particularly, in the lateral compartment, was found to be significantly associated with increased pain 7 .…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…OA is considered a disease of the whole joint, affecting not only the articular cartilage but extending to the bone tissue and synovium. Bone damage in PTOA, such as the thickening of the area below the calcified cartilage (subchondral bone and trabecular bone) and osteophyte formation, can appear early during disease progression, and such structural changes can contribute to OA pain and disability [ 6 , 9 , 29 , 30 ]. Therefore, in the effort to find therapeutic intervention to limit OA progression, bone tissue constitutes an important target.…”
Section: Discussionmentioning
confidence: 99%
“…As a protective mechanism, the body responds by producing osteophytes, which are bony outgrowths, in an attempt to stabilize the joint. These structural changes contribute to the development of FFD by altering the joint mechanics and placing abnormal stresses on the surrounding soft tissues [7] . The clinical implications of FFD in knee OA are significant.…”
Section: Fig (1)mentioning
confidence: 99%